Identification of the Recently Described Avian Hepatitis E Genotype 7 in an Outbreak of Hepatitis-Splenomegaly Syndrome (HSS) with High Mortality and Severe Drop in Egg Production in a Parent Stock Flock in Bangladesh - Miguel Matos; Ivana Bilic; László Kőrösi; Rakibul Hasan; Dieter Liebhart; Nicola Palmieri; Michael Hess (Poultry, 2025)
This study reports an outbreak of hepatitis-splenomegaly syndrome (HSS) in a color broiler parent stock flock in Bangladesh, marking the first known instance of HSS associated with avian hepatitis E virus (aHEV) genotype 7 outside Europe and only the second report of HSS in South Asia. The affected flock exhibited severe clinical signs, including a high cumulative mortality, reaching 31.6% in hens, and an abrupt decrease in egg production, dropping by over 20 percent. Histopathological analysis of liver and spleen samples revealed multifocal areas of necrosis, hemorrhages, and bacterial colonies. RT-PCR confirmed the presence of aHEV and immunohistochemistry showed signals within hepatic sinusoids and peri-ellipsoidal zones in the spleen. Complete genome sequencing of RNA from liver and bile samples on the Illumina platform established a pathogenic link to aHEV genotype 7. Despite aHEV’s known association with HSS, inconsistencies in disease manifestation suggest additional cofactors influencing pathogenesis, with secondary bacterial infections potentially contributing to clinical severity in this outbreak. Overall, this case expands the geographic distribution of aHEV genotype 7 and highlights the need for further epidemiological studies to investigate genotype–pathogenicity associations, especially in regions with limited prior data on HSS.